Effects of the Lorentz symmetry violation on relativistic neutral scalar bosons: Scattering and bound states - Castro, Luis B.; de Castro, Antonio S. [UNESP] (IOP Publishing, 2025)
In this letter, we investigate the effects of Lorentz symmetry violation on a relativistic neutral scalar boson within the framework of the Klein-Gordon formalism. We consider a tensor out of the Standard Model Extension, which describes the field configuration consisting of a constant magnetic field and a cylindrical electric field . We analyze and discuss the effects of Lorentz symmetry violation on the equation of motion and show that the presence of a specific Lorentz symmetry violation parameter is essential to obtain analytical solutions for scattering and bound states. Employing the partial wave approach in cylindrical coordinates, we calculate the relativistic phase shift, scattering amplitude and S-matrix, and discuss the effects of Lorentz symmetry violation on the phase shift. Furthermore, we obtain bound-state solutions by examining the poles of the S-matrix and compare our findings with those reported in the literature. Our results reveal that bound-state solutions are only feasible for a restricted range of Lorentz symmetry violation parameters, which contradict previous studies.